BIMBINGAN DAN PELATIHAN PENERAPAN ETIKA BISNIS UNTUK MENINGKATKAN PENGETAHUAN DAN KEMAMPUAN IBU-IBU WARGA VILLA SENGKALING DESA MULYOAGUNG KECAMATAN DAU KABUPATEN MALANG - Siti Nurbaya; Rulirianto Rulirianto; Bambang Suryanto; Ellyn Eka Wahyu; Fatkhur Rohman (Dharma: Jurnal Pengabdian Masyarakat, 2021)
Since the Covid-19 outbreak, resulted some health crisis and also disrupted economic activity. From these conditions, it could be seen that the SME’S sector (that majority were the lower middle class) had been heavily affected by the Covid-19 pandemic. This activity that held by PKM team in 2021 was aimed to provided education to all of entrepreneur that do some business in food and beverages regarding business ethics during the COVID-19 pandemic. This activity was carried out at the Sengkaling Villa Meeting Hall, attended by 20 participants. To implemented our service activities was done by transferring knowledge and discussing some questions and also give the answers. Evaluation of participants' understanding was done by distributing questionnaires. Knowledge transfer was carried out by giving presentations on the meaning and purpose of business ethics, business ethics according to the teachings of the Prophet Muhammad and also business ethics during the Pandemic. This activity received a positive response from the training participants and we hoped that the target audience will continue to upgraded services in the food and beverages sector so that businesses could survived during the pandemic while maintained good business ethics.